The Bible and Jews in medieval Spain - Roth, Norman (Studies in Medieval History and Culture Ser., 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Dedication -- Table of Contents -- Table -- Preface -- List of Abbreviations -- 1 The Bible and its Interpretation: In Muslim Spain -- 2 Abraham Ibn 'Ezra -- 3 Ibn 'Ezra, Part 2 -- 4 Christian Spain, Part 1: Provence, Catalonia, Aragón (to Fourteenth Century) -- 5 Christian Spain, Part 2: Aragón-Catalonia Fourteenth Century -- 6 Bible Texts in Spain: Manuscripts, Editions and Translations -- Appendix 1: Sources and Names Cited by Ibn 'Ezra, Qimḥi and Naḥmanides -- Appendix 2: Commentaries by Name of Book and of Author -- Bibliography -- Index.